Critical Infrastructure Risks - Senovsky, Michail; Senovsky, Pavel (Communications - Scientific letters of the University of Zilina, 2008)
Critical infrastructure can be taken as aphenomenon of recent time. Not only theory but also practice has shown that solving problems of the protection of critical infrastructure, especially ensuring its functionality, is a necessary precondition for the operation of public authorities, services, the viability of aregion, area or country. The first step to protect the critical infrastructure must be the identification of risks endangering the security of single systems or elements. The contribution deals with the problems of searching for and denoting these risks and by looking for their interrelations.